Joint action, intended meaning and (statutory) interpretation - Ekins, R (University of San Diego, 2021)
Smith and Jones (singular) is an exporting firm, an agent. It is formed by two partners, Smith and Jones (plural), acting jointly and is thus a small purposive group. Mary is the firm’s employee. She forms part of the group insofar as her acts will be acts of the firm. Mary acts on written instructions, which means that Smith and Jones jointly direct Mary by way of instructions to which they both agree, the agreement of each partner being signified by each signing a memorandum. Smith and Jones jointly stand to Mary as superior to inferior. The firm has a decision-making structure—a standing intention to form further, particular intentions—to this extent. Smith and Jones stand to one another as equals. The firm is to this extent a simple group in which joint action and intention requires unanimity on the part of Smith and Jones. This is the default for group action. Smith and Jones might adopt a rule—a standing intention—that each would be committed to the other’s reasonable misunderstandings of proposals he makes. The rule that Mary’s instructions are only operative if signed by both partners might suggest this. However, this rule is just as readily understood as requiring, and constituting, a written record of (true) agreement.